A review of benefits and potential application of flavonoids in citrus - Azlinda, Ali; Zarina, Zakaria, Dr.; Ku Syahidah, Ku Ismail (Universiti Malaysia Perlis (UniMAP), 2012)
Engineering Postgraduate Conference 2009 (EPC 2009) organized by Postgraduate Studies Office and Research & Development (R&D) Unit, Universiti Malaysia Perlis (UniMAP) on 18-19 July 2009 at Dragon and Phoenix, Jejawi, Perlis, Malaysia.